ATS drugs molecular structure representation using refined 3D geometric moment invariants - Draman @ Muda, Azah Kamilah; Pratama, Satrya Fajri; Choo, Yun Huoy; Flusser, Jan; Abraham, Ajith (Springer International Publishing, 2017)
The campaign against drug abuse is fought by all countries, most notably on ATS drugs. The identification process of ATS drugs depends heavily on its molecular structure. However, the process becomes more unreliable due to the introduction of new, sophisticated, and increasingly complex ATS molecular structures. Therefore, distinctive features of ATS drug molecular structure need to be accurately obtained. In this paper, two variants of refined 3D geometric moment invariants for ATS drug molecular structure representation are discussed. This paper is also meant for comparing the performance of these two variants. The comparison was conducted using drug chemical structures obtained from Isomer Design’s PiHKaL.info database for the ATS drugs, while non-ATS drugs are obtained randomly from ChemSpider database. The assessment highlights the best technique which is suitable to be further explored and improved in the future studies so that it is wholly attuned with ATS drug molecular similarity search domain.